Highlighting Differences in Cancer Epidemiology in India: A Descriptive Report from a Private Sector Hospital-Based Cancer Registry in Delhi for the Years 2013 to 2017 - Shrivastav, Gunjan; Adhana, Arun; Kumari, Kamlesh; Khan, Naseem; Kumar, Ankit; Rathore, Shailender; Anand, Anil Kumar; Arora, Ramandeep Singh (Indian Journal of Medical and Paediatric Oncology, 2021)
Introduction Cancer continues to grow in number. Knowing the epidemiology helps in prevention and treatment. Existing hospital-based cancer registries (HBCRs) provide little data of private sector including patients for medical tourism.Objectives The aim of this study was to describe the distribution of cancer at a tertiary center in the private sector in North India for all cancer patients.Materials and Methods Cases were ascertained from the Oncology Outpatient Department of Max Super Specialty Hospital, Saket, between January 1, 2013, and December 31, 2017, and from pathology database since July 2015. They were abstracted into National Cancer Registry Program (NCRP) core pro forma. We conducted a descriptive analysis of distribution by age, gender, nationality, site, stage, and treatment.Results Among the 15,850 confirmed cases, 8,034 (51%) were males. Nearly 1.8% of patients were pediatric (<15 years) and 30.1% geriatric (>65 years). A high proportion of patients (13%) came from outside India and 27% from outside Delhi-National Capital Region. The most common cancers in males were prostate (10.9%), lung (10%), and mouth (7.6%). Stomach was the most common site of cancer in international male patients. Four of the top ten cancers in males were of the gastrointestinal tract (esophagus, stomach, colon, and rectum). The most common cancers in females were breast (37.4%), ovary (7.1%), and corpus uteri (5.6%). Tobacco-related cancers accounted for 36.9% of cancers in males and 11.3% in females. The composite stage in males was IV in 54%, followed by stage III (21%), stage II (15%), and stage I (10%). In females, stage IV was 33%, stage III was 23%, stage II was 28%, and stage I was 16%. As registry included outpatient record visits and pathology records, not all registered patients received treatment at Max Super Specialty Hospital. Overall, 49.8% of male patients and 49.7% of female patients received treatment at Max Super Specialty Hospital. Data quality metrics matched other national HBCRs.Conclusion We highlight the differences from other NCRP HBCRs, with prostate cancer being the top cancer in males and gastrointestinal cancers forming major proportion among all. Socioeconomic status of our patients, referral bias, and international medical tourism could be responsible.
Keywords: cancer; epidemiology; hospital-based cancer registry; India; medical tourism